Privasi rumah kediaman dalam perundangan Islam sebagai langkah pencegahan kepada keganasan domestik - Zahari Mahad Musa (Pejabat Karang Mengarang (UPSI Press), Universiti Pendidikan Sultan Idris, 2024)
Domestic violence refers to violence and predatory behaviour in a household, and it has a significant impact to the institution of the family. Personality control and quality environment is a basis for addressing this crisis from recurring. The dwelling house is part of the environment and has a close relationship with the family. Family development and its well-being start with a good and quality dwelling house. This is because the dwelling house is not just merely a physical space, but it is a place where its occupants start to build a well-being and harmonious relationship as a small community. Islam prescribes three main requirements for a quality dwelling house namely healthy, safety and privacy. This study discusses privacy as related to the dwelling house in Islamic law as one of the preventive measures in dealing with the problem of domestic violence. The analysis is based on Islamic jurisprudence sources and Islamic scholars deliberations on the concept of privacy. The findings showed that Islam prescribed integrated rules and regulations with regard to dwelling houses in order to ensure the well-being of the family. The privacy protection set by Islamiclaws guarantee prosperous life among residents and indirectly acts as preventive measures in addressing domestic violence.